An Analysis of Politeness Strategies used by the Students in Conversation - Sembiring, Lina Tri Astuty Beru; Rullyanti, Merry; Bintang, Ahmad Hasyimi Arow; Rahmawati, Ambar (Journal Of Dehasen Educational Review, 2020)
Politeness is influenced by cultural background, social background, historical and geographical elements. Encouraging students regarding the importance of having politeness strategies in communicating will develop their awareness not only in communicative competence but also cultural awareness, and build their character values. This research aims to explore the use of politeness strategies that occur in English class interactions for first semester students of the Early Childhood Education Study Program in 2022. This research uses a descriptive qualitative research design to explore the politeness strategies used by teachers and students in their interactions. The participants in this study were an English teacher and 32 students. The data in this research are utterances that contain politeness strategies. The data was taken from a 90 minute English lesson which was video recorded. The results showed that there were 7 citations containing three politeness strategies: positive politeness strategies, negative politeness strategies and bald-on-record politeness strategies. The interaction is dominated by the teacher. In addition, the politeness strategies that occur in class interactions are influenced by several factors such as differences in age, institutional position, power, and social distance. Keyword: Classroom Interactions, Politeness, Politeness Strategies